2021
DOI: 10.1111/pai.13696
|View full text |Cite
|
Sign up to set email alerts
|

Asthma as a risk factor for hospitalization in children with COVID‐19: A nested case‐control study

Abstract: Background Most pediatric studies of asthma and COVID‐19 to date have been ecological, which offer limited insight. We evaluated the association between asthma and COVID‐19 at an individual level. Methods Using data from prospective clinical registries, we conducted a nested case‐control study comparing three groups: children with COVID‐19 and underlying asthma (“A+C” cases); children with COVID‐19 without underlying disease (“C+” controls); and children with asthma wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 45 publications
0
46
0
1
Order By: Relevance
“…27 In contrast, a recent nested case-control study of 1,392 children in Western Pennsylvania found that children with asthma who became infected with SARS-CoV-2 were four times more likely to be hospitalized than SARS-CoV-2-infected children without asthma, though length of stay and respiratory support did not differ between these groups. 28 It is also possible that asthma severity could influence SARS-CoV-2 outcomes among children. A study of over 700,000 children in Scotland found that SARS-CoV-2-infected children with poorly controlled asthma were at higher risk of hospitalization for COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…27 In contrast, a recent nested case-control study of 1,392 children in Western Pennsylvania found that children with asthma who became infected with SARS-CoV-2 were four times more likely to be hospitalized than SARS-CoV-2-infected children without asthma, though length of stay and respiratory support did not differ between these groups. 28 It is also possible that asthma severity could influence SARS-CoV-2 outcomes among children. A study of over 700,000 children in Scotland found that SARS-CoV-2-infected children with poorly controlled asthma were at higher risk of hospitalization for COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Asthma was identified here as a risk factor for CCU admission for both age groups (<> 2 years old). Recent studies have also shown the involvement of asthma in the risk of hospital admission but not of CCU admission ( 7 , 28 ). This increased risk of hospitalization, primarily for children with poorly controlled asthma ( 29 ), was not related to asthma severity, and SARS-CoV-2 infection did not appear to be a trigger exacerbation of asthma ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the association between asthma and SARS-CoV-2 infection remains unclear in the pediatric population, as many large-scale ecological studies presented reduced pediatric asthma during the pandemic likely due to physical distancing, masks, and perhaps decreases in air pollution. On the other hand, other research focused on the individual level and presented asthma as a risk factor for hospitalization in children with COVID-19, but not for worse COVID-19 outcomes (24,25).…”
Section: Discussionmentioning
confidence: 99%